Chemoprevention curcumin analog 1.1 promotes metaphase arrest and enhances intracellular reactive oxygen species levels on TNBC MDA-MB-231 and HER2-positive HCC1954 cells - Dhania Novitasari; Riris Istighfari Jenie; Jun-ya Kato; Edy Meiyanto (Wolters Kluwer Medknow Publications, 2023)
Background and purpose : Previous studies highlighted that chemoprevention curcumin analog-1.1 (CCA-1.1) demonstrated an antitumor effect on breast, leukemia, and colorectal cancer cells. By utilizing immortalized MDA-MB-231 and HCC1954 cells, we evaluated the anticancer properties of CCA-1.1 and its mediated activity to promote cellular death. Experimental approach : Cytotoxicity and anti-proliferation were assayed using trypan blue exclusion. The cell cycle profile after CCA-1.1 treatment was established through flow cytometry. May-Grünwald-Giemsa and Hoechst staining were performed to determine the cell cycle arrest upon CCA-1.1 treatment. The involvement of CCA-1.1 in mitotic kinases (aurora A, p-aurora A, p-PLK1, and p-cyclin B1) expression was investigated by immunoblotting. CCA-1.1-treated cells were stained with the X-gal solution to examine the effect on senescence. ROS level and mitochondrial respiration were assessed by DCFDA assay and mitochondrial oxygen consumption rate, respectively. Findings/Results : CCA-1.1 exerted cytotoxic activity and inhibited cell proliferation with an irreversible effect, and the flow cytometry analysis demonstrated that CCA-1.1 significantly halted during the G2/M phase, and further assessment revealed that CCA-1.1 caused metaphase arrest. Immunoblot assays confirmed CCA-1.1 suppressed aurora A kinase in MDA-MB-231 cells. The ROS level was elevated after treatment with CCA-1.1, which might promote cellular senescence and suppress basal mitochondrial respiration in MDA-MB-231 cells. Conclusion and implications : Our data suggested the in vitro proof-of-concept that supports the involvement in cell cycle regulation and ROS generation as contributors to the effectiveness of CCA-1.1 in suppressing breast cancer cell growth.